Medicinal Plants Potential of Olele Village, Kabila Bone Sub-district as Ecotourism Support - Moh G. H. Sahada; Jusna K. Ahmad; Abubakar S. Katili (The Ethnobiological Society of Indonesia, 2022)
Olele is a village with quite high tourism potential, one of which is medicinal plants which are quite high and varied. This study aimed to identify species of medicinal plants in the village and identify their potential as ecotourism support. It was conducted using an indepth interview technique with a qualitative type. The data obtained will then be documented and identified using the book and the Plant-Net application. The results showed that 17 species of medicinal plants were identified from the results of interviews, and then validation was carried out on domestic tourists who were in the village to find out the personal interests of each tourist. The development of tourist areas has also been responded positively by the community and local government.